Symptoms, antibody levels and vaccination attitude after asymptomatic to moderate COVID-19 infection in 200 healthcare workers - Harsch, Igor Alexander; Ortloff, Andrea; Reinhöfer, Mike; Epstude, Jörg (German Medical Science GMS Publishing House, 2021)
Aim: In Germany, the willingness to be vaccinated against COVID-19 is rather low among medical staff. We collected data on symptoms, antibody titers and vaccination readiness from clinic employees at a municipal clinic who had already been through a COVID-19 infection (asymptomatic to moderate). We also examined the antibody titers for their possible importance as an individual decision-making aid with regard to vaccination.Method: 200 employees of our municipal clinics were included in the study. COVID-19 antibody determination was performed using an ELISA (EUROIMMUN™, PerkinElmer, Inc. Company). The participants were given an anonymous questionnaire containing anthropometrical issues, symptoms of the infection and questions concerning the vaccination decision. Finally, the antibody levels were reported to the participants and the attitude towards a vaccination was reevaluated.Results: In all 200 participants who had already gone through a COVID-19 infection, 75 employees were in favor of a vaccination (37.5%), 96 were opposed to vaccination (48%), and 29 were undecided (14.5%). In the different occupational groups, the positive trend in terms of willingness to be vaccinated was highest among physicians and is least among nurses. The antibody results showed considerable variation in titer levels and therefore did not correlate with disease severity in asymptomatic to moderately ill persons. We also observed a pro-vaccination trend with increasing age of the participants. The specifically-asked symptom of cutaneous hyperesthesia during COVID-19 infection occurred in 5% of the participants.Conclusion: In medical personnel who had already suffered from a COVID-19 infection, the willingness to receive a vaccination tends to be highest among physicians, and lowest in nurses, and increases with age. For the vast majority of those affected, knowledge of the antibody titers only reinforces the vaccination decision made beforehand and thus does not contribute to a change in vaccination decision. The specifically-requested symptom of cutaneous hyperesthesia during COVID-19 infection was unexpectedly frequent.